PENGEMBANGAN MP-ASI LOKAL UNTUK MEMPERSIAPKAN GENERASI EMAS 2045 DAN PEMBERDAYAAN PROGRAM STBM SERTA MENCAPAI DESA ODF DI DESA CABANG EMPAT KECAMATAN ABUNG SELATAN, KABUPATEN LAMPUNG UTARA - Sri Sumardilah, Dewi; Indriyani, Reni; Muliani, Usdeka; Prianto, Nawan; Sutarto (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
This Community Service Program, conducted under the Village Partner Development Scheme, is titled "Development of Local MP-ASI to Prepare the Golden Generation 2045 and Empower the STBM Program to Achieve ODF Village in Cabang Empat Village, Abung Selatan District, North Lampung Regency. The primary objective of this activity is to enhance the skills of community health cadres in preparing MP-ASI and to increase the community's capacity to implement Community-Based Total Sanitation (STBM) toward achieving ODF (Open Defecation Free) Village status. The specific objectives of this program are: Training participants in preparing MP-ASI using locally sourced food ingredients. Providing assistance in the construction and installation of latrines. Achieving ODF Village status. According to the 2019 Indonesian Toddler Nutrition Status Survey (SSGI), the prevalence of stunted toddlers in Lampung Province decreased from 42.6% in 2013 to 26.3% in 2019. However, in North Lampung Regency, the prevalence increased from 32.44% in 2013 to 38.56% in 2019. Stunting is a health issue caused by insufficient nutritional intake during the first 1,000 days of life. One of the leading causes of stunting in Lampung Province is suboptimal balanced nutrition intake and low coverage of Early Growth and Development Detection and Intervention Stimulation for toddlers. Cabang Empat Village, located in Abung Selatan District, is identified as a stunting locus village in North Lampung Regency, with 15 recorded cases of stunted toddlers. Through this program, it is hoped that the community will develop a better understanding of the importance of balanced nutrition and proper sanitation to prepare the Golden Generation 2045 and achieve ODF Village status. — Program Pengembangan Desa Mitra ini adalah inisiatif pengabdian kepada masyarakat untuk mengembangkan MP-ASI lokal dan memberdayakan Program Sanitasi Total Berbasis Masyarakat (STBM) guna mencapai status Desa ODF (Open Defecation Free) di Desa Cabang Empat, Kecamatan Abung Selatan, Kabupaten Lampung Utara. Kegiatan ini menggunakan pendekatan pemberdayaan masyarakat dan pemberian stimulan dengan tujuan utama meningkatkan keterampilan kader dalam menyiapkan MP-ASI lokal serta kemampuan masyarakat dalam melaksanakan STBM menuju Desa ODF. Tujuan khusus dari program ini meliputi: 1) praktik membuat MP-ASI berbahan makanan lokal, 2) pendampingan pembuatan dan pemasangan jamban, dan 3) mencapai predikat desa ODF. Metode pelaksanaan mencakup ceramah, diskusi, praktik, dan pemberian stimulan. Ceramah-diskusi digunakan untuk sosialisasi program dan lokakarya, sementara praktik dilakukan dalam pembuatan MP-ASI dan kloset serta pemberian stimulan untuk pembuatan jamban keluarga. Menurut Survei Status Gizi Balita Indonesia (SSGI) 2019, prevalensi balita stunting di Provinsi Lampung menurun dari 42,6% pada 2013 menjadi 26,3% pada 2019. Namun, di Kabupaten Lampung Utara, prevalensinya meningkat dari 32,44% menjadi 38,56%. Stunting, yang disebabkan oleh kurangnya asupan gizi selama seribu hari pertama kehidupan (HPK), masih menjadi masalah di Provinsi Lampung. Desa Cabang Empat adalah salah satu desa locus stunting di Kabupaten Lampung Utara, dengan 15 balita stunting. Program ini diharapkan dapat meningkatkan pemahaman masyarakat akan pentingnya gizi seimbang dan sanitasi, serta membantu mempersiapkan generasi emas 2045 dan mencapai desa ODF.